All-ceramic or metal-ceramic tooth-supported fixed dental prostheses (FDPs)? A systematic review of the survival and complication rates. Part II: Multiple-unit FDPs. Issue 6 (June 2015) - Pjetursson, Bjarni Elvar; Sailer, Irena; Makarov, Nikolay Alexandrovich; Zwahlen, Marcel; Thoma, Daniel Stefan
Abstract: Objective: To assess the 5-year survival of metal-ceramic and all-ceramic tooth-supported fixed dental prostheses (FDPs) and to describe the incidence of biological, technical and esthetic complications. Methods: Medline (PubMed), Embase and Cochrane Central Register of Controlled Trials (CENTRAL) searches (2006–2013) were performed for clinical studies focusing on tooth-supported FDPs with a mean follow-up of at least 3 years. This was complemented by an additional hand search and the inclusion of 10 studies from a previous systematic review[1] . Survival and complication rates were analyzed using robust Poisson's regression models to obtain summary estimates of 5-year proportions. Results: Forty studies reporting on 1796 metal-ceramic and 1110 all-ceramic FDPs fulfilled the inclusion criteria. Meta-analysis of the included studies indicated an estimated 5-year survival rate of metal-ceramic FDPs of 94.4% (95% CI: 91.2–96.5%). The estimated survival rate of reinforced glass ceramic FDPs was 89.1% (95% CI: 80.4–94.0%), the survival rate of glass-infiltrated alumina FDPs was 86.2% (95% CI: 69.3–94.2%) and the survival rate of densely sintered zirconia FDPs was 90.4% (95% CI: 84.8–94.0%) in 5 years of function. Even though the survival rate of all-ceramic FDPs was lower than for metal-ceramic FDPs, the differences did not reach statistical significance except for the glass-infiltrated alumina FDPs ( p  = 0.05). A significantly higher incidence of caries in abutment teeth was observed for densely sintered zirconia FDPs compared to metal-ceramic FDPs. Significantly more framework fractures were reported for reinforced glass ceramic FDPs (8.0%) and glass-infiltrated alumina FDPs (12.9%) compared to metal-ceramic FDPs (0.6%) and densely sintered zirconia FDPs (1.9%) in 5 years in function. However, the incidence of ceramic fractures and loss of retention was significantly ( p  = 0.018 and 0.028 respectively) higher for densely sintered zirconia FDPs compared to all other types of FDPs. Conclusions: Survival rates of all types of all-ceramic FDPs were lower than those reported for metal-ceramic FDPs. The incidence of framework fractures was significantly higher for reinforced glass ceramic FDPs and infiltrated glass ceramic FDPs, and the incidence for ceramic fractures and loss of retention was significantly higher for densely sintered zirconia FDPs compared to metal-ceramic FDPs.